PRICE AND ONLINE REVIEWS’ INFLUENCES ON ACCOMMODATION PURCHASE DECISIONS IN BALI THROUGH AIRBNB - Maria Pia Adiati; Cindy Sophia (Jurnal Ilmiah Hospitality, 2023)
The research objective is to find out whether Price and Online review are influencing tourists to make decisions in accommodation booking in Bali through Airbnb and what factors are most influential. This study uses quantitative methods in which researchers gather data and then the data is measured using SPSS. The questionnaire was conducted with 13 questions and distributed on June 1 - June 10, 2020, and there were 130 respondents. Based on the results of the study, a validity test and a reliability test have been conducted to obtain the feasibility of the study. When the results are feasible then continues by testing the hypothesis, normality, correlation, simple linear regression and multiple regression of the answers given by respondents to find out how much the relationship and influence between variables Price (X1) and Online review(X2) on variable Customer decision (Y). In this research Online review has bigger influence compared to Price. Price and Online Reviews also have a positive and significant influence on customer decisions.